Efficacy and Safety of Sofosbuvir and Ribavirin for Treating Chronic Hepatitis C, Genotype 3: Experience of a Tertiary Care Hospital at Karachi, Pakistan - Butt, Nazish (Cureus, 2019)
Background It is estimated that approximately 10 million individuals in Pakistan are infected with hepatitis C virus (HCV). Historically, it was very difficult not just to cure but even treat HCV as available options did not have desirable outcomes. However, the approval of directly acting antiviral (DAA) drugs has revolutionized treatment and management. These are specific proteases and polymerase inhibitors with profound capability for accomplishing elimination and overtime eradication of the virus. Objective The aim of this study was to evaluate the efficacy and safety of sofosbuvir (SOF) in combination with ribavirin (RIB) for the treatment of chronic hepatitis C virus with genotype 3. Materials and methods This prospective observational study was conducted at the gastroenterology section of Medical Unit IV, Jinnah Post-graduate Medical Center, Karachi and Medical Unit II, Dow University of Health Sciences, Ojha Campus, Karachi from January 2016 to December 2016. Patients aged 18 years or older of either gender having chronic active HCV infection as demonstrated by a positive Anti-HCV (ELISA) test and a qualitative polymerase chain reaction (PCR) analysis along with genotype analysis showing only type 3 were inducted into the study. Treatment was initiated with either 12-week or 24-week regimen of SOF 400 mg once daily along with weight-adjusted RIB orally. Successful treatment was indicated by the elimination of the virus, i.e., undetectable viral load/levels by PCR qualitative analysis. Rapid virological response (RVR), end of treatment response (ETR), and sustained virological response (SVR) were defined as the undetectable viral load at four, 12, and 24 weeks, respectively. Results A total of 300 patients were inducted into the study, predominantly female (57%). The mean age of presentation was 41.14 ± 11.48, and most (70.33%) were treatment naïve. The mean alanine transaminase (ALT), aspartate aminotransferase (AST), and gamma-glutamyl transferase (GGT) levels at presentation were 41.89 ± 46.23 IU/l, 68.57 ± 83.62 IU/l, and 54.52 ± 77.57 IU/l, respectively. ALT, AST, and GGT levels at 24 weeks were 33.84 ± 13.60 IU/l, 32.44 ± 16.16 IU/l, and 37.59 ± 22.41 IU/l, respectively, showing significant improvement. ETR was achieved in 99.1% (209) treatment-naïve patients and 98.9% (88) treatment-experienced patients. SVR rates were almost similar with 98% (208) achieving it in the treatment-naïve group and 96.6% (86) achieving it in the treatment-experienced group. Conclusion SOF in combination with RIB is safe and remarkably efficacious in the treatment of chronic HCV, genotype 3. Not only is this regimen associated with the elimination of viral replication but it also improved transaminase levels. Outcomes are rarely, if ever, affected by previous use of antiviral medications.